2019
DOI: 10.1016/j.jobcr.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue facial profile changes after orthodontic treatment with or without tooth extractions in Class I malocclusion patients: A comparative study

Abstract: To analyze the soft tissue facial profile changes in Class I malocclusion patients after orthodontic treatment with or without tooth extraction. Methods: Forty lateral cephalograms of 20 individuals with Angle Class I malocclusion submitted to orthodontic treatment were included in this study. The individuals were divided in two groups: no tooth extraction (Group A) and extraction of four first premolars (Group B). Cephalometric measurements related to the soft tissue facial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 27 publications
1
17
0
3
Order By: Relevance
“…According to rickets et al, the ratio of 0.6:1 symbolizes the golden proportion which the standard for an aesthetically attractive profile. The maximum changes in the anthropometric parameter were observed in an orthodontic group, statistical significance was upper lip length, lower lip length, upper vermillion show, lower vermillion which was in concordance with a study done by Benedito V. Freitas et al [17] .…”
Section: Discussionsupporting
confidence: 91%
“…According to rickets et al, the ratio of 0.6:1 symbolizes the golden proportion which the standard for an aesthetically attractive profile. The maximum changes in the anthropometric parameter were observed in an orthodontic group, statistical significance was upper lip length, lower lip length, upper vermillion show, lower vermillion which was in concordance with a study done by Benedito V. Freitas et al [17] .…”
Section: Discussionsupporting
confidence: 91%
“…Lee et al reported that extraction of the four premolars led to significantly greater retraction of the upper/lower lip from Ricketts’ E plane [ 22 ] Liu et al reported a significantly smaller lip vermilion after extraction, indicating that the lip vermilion was more slender when the mouth height–width ratio was decreased [ 10 ]. Nevertheless, contradicting conclusions drawn by Freitas et al [ 23 ], and Ayhan Basciftci et al [ 24 ] reported that extraction of the first premolars did not imply a greater degree of retraction in the lip soft tissue. A more harmonious vermilion was considered attractive and had positive effects on lip aesthetics [ 5 ], but the relationship between lip morphology and facial aesthetics is complex.…”
Section: Discussionmentioning
confidence: 79%
“…Liu et al reported a significantly smaller lip vermilion after extraction, indicating that the lip vermilion was more slender when the vermilion height-width ratio was decreased [10]. Nevertheless, contradicting conclusions drawn by Freitas et al [18] and Basciftci et al [19] reported that extraction of first premolars did not imply a greater degree of retraction in lip soft tissue. A more harmonious vermilion was considered attractive and had positive effects on lip esthetics [5], but the relationship between lip morphology and facial esthetics is complex.…”
Section: Resultsmentioning
confidence: 94%